Pengembangan Media Pembelajaran Interaktif Berbasis Macromedia Flash Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Bunial Khawarizmi; Ketut Sarjana; Dwi Novitasari; Nyoman Sridana (Mandalika Mathematics and Educations Journal, 2024)
This study aims to develop interactive learning media based on Macromedia Flash to improve student motivation and learning outcomes that are valid, practical, and effective. This research and development study uses the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of the study are eighth-grade students at MTs Al-Aziziyah Putra Gunungsari. Data analysis was conducted using both quantitative and qualitative descriptive methods regarding the validity of the learning media, which was obtained from validation sheets, the practicality of the learning media, which was obtained from questionnaires filled out by students and teachers regarding the learning media, and the effectiveness of the learning media, which was obtained from questionnaires on student motivation and pretest and posttest results.The results of the study indicate that: (1) the interactive learning media based on Macromedia Flash developed in this study is valid, with an average validation score of 0.82, categorized as very valid; (2) the interactive learning media based on Macromedia Flash developed is practical, with an average practicality score of 90.32%, categorized as very practical; (3) the interactive learning media based on Macromedia Flash developed is effective, as seen from the increase in student motivation with an N-gain score of 76.5%, categorized as high. Additionally, there was an improvement in student learning outcomes with an N-gain score of 56.11%, categorized as moderate. Therefore, the interactive learning media based on Macromedia Flash is suitable for enhancing student motivation and learning outcomes.